Keindahan dalam Disabilitas: Sebuah Konstruksi Teologi Disabilitas Intelektual - Isabella Novsima Sinulingga (Indonesian Journal of Theology, 2015)
This article challenges conceptions of intellectual disability that view such conditions from the perspective of normalcy. In Indonesia, conversations of theological anthropology still employ a medical model lens, which perceives disability merely as bodily and intellectual impairments, thus failing the standard of "normal." Normalcy unilaterally defines disability and dictates normative approaches toward persons with disabilities. Consequently, persons with disabilities are perceived in Indonesia as mere objects of charity to be pitied. On the other hand, they remain susceptible to suffering violence. These trends owing to the fact that Indonesian society does not adequately provide either tangible resource considerations or sufficient social support. Lacunae in the theological literature concerning disability in Indonesian contexts foment in the life of the church further challenges for persons with disabilities. For persons there with intellectual disabilities, in particular, the situation is even more severe, as their condition is regarded as a kind of punishment for sin and further stigmatized as abnormal. This article offers a constructive theology of disability to dismantle the myth of normalcy, which reduces persons with disabilities to being merely impaired organisms within society. Theological musings on the beauty of all creation, the perichoretic relationship within the Trinity, the doctrines of imago Dei and imago Christi are taken up in this essay, to offer an inclusive theology expressly for persons with intellectual disabilities.